Potensi Ekstrak Eleutherine palmifolia(L) Merr dalam Menghambat Pertumbuhan Escherichia coli galur Extended Spectrum Beta Lactamase - Ni Made Susilawati; Neiny Prisy Foekh (JURNAL KEPERAWATAN SISTHANA, 2021)
Infection prevention therapy generally uses antibiotics (Priyanto, 2009) where inappropriate use of antibiotics (Paterson, et al., 2005) can cause resistance to antibiotics. Increasing bacterial resistance to antibiotics provides a great opportunity to obtain antibacterial compounds by utilizing the diversity of plants in Indonesia (Manik et al, 2018). Dayak onions on Lembata Island are known as forest onions, their alkaloid content has an antimicrobial function. This research aims to further study the potential of Dayak onion bulbs / forest onions (Eleutherine palmifolia) (L) Merr taken from the Lembata area, East Nusa Tenggara, in inhibiting the growth of Gram-negative Escherichia coli bacteria which include the Extended Spectrum Beta Lactamase (ESBL) strain. ) with Escherichia coli bacteria. Dayak onion 96% ethanol extract was made in a concentration of 10% to 100% which was tested with ESBL strain Escherichia coli bacteria, the inhibitory power formed was measured to determine the Minimum Inhibitory Concentration (MIC) value. Data obtained from Dayak onion (Eleutherine palmifolia) L (Merr) ethanol powder extract has antimicrobial activity in inhibiting the growth of Escherichia coli bacteria in Dayak onion (Eleutherine palmifolia) L (Merr) ethanol powder extract at concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% of Escherichia coli bacteria is a concentration that is included in the weak group.